Characterization of young infants with fecal carriage of multidrug-resistant Escherichia coli in Southern Taiwan - Fang-Chih Lin; Wailap Victor Ng; Hsiao-Ping Wang; Chih-Hsin Hung; Jenn-Tzong Chang; Chih-Chieh Yang; Po-Yen Liu; Ming-Fang Cheng (Elsevier, 2024)
Background: The accelerating prevalence of extended-spectrum β-lactamase (ESBL)-producing and multidrug-resistance (MDR) Escherichia coli (E. coli) become a public health challenge worldwide. This study aimed to discuss the prevalence of drug-resistant E. coli colonization and analyze its risk factors and clinical characteristics among young infants in Southern Taiwan. Methods: Stool samples were collected from young infants, aged less than three months, within three days of their hospitalization from September to December 2019 in a tertiary hospital. A questionnaire was designed for parents to complete. E. coli colonies were selected and analyzed for antimicrobial susceptibility. PCR-based multilocus sequence typing was to detect the presence of sequence type ST131 and blaCTX-M genes. Results: Among 100 enrolled infants, 36% had fecal carriage of E. coli isolates, of which twenty nine (80.5%) were MDR, thirteen (36.1%) were ESBL-producing isolates and five (13.8%) and ten (27.7%) were ST131 and strains carrying CTX-M-14 gene, respectively. Compared to non-ST131 and non-CTX-M-14 gene carrier, isolates of ST131 and CTX-M-14 gene carrier showed a significantly higher resistance rate to cefixime, ceftriaxone, and gentamycin, with p value all <0.05. Conclusion: The prevalence of ESBL-producing and MDR E. coli fecal carriage were both high in young infants. The most common sequence type is ST131, of which all are strains carrying CTX-M-14. Further surveillance and investigation to control for the high prevalence of antimicrobial-resistant E. coli fecal carriage among infants in Taiwan are warranted.